Factors Affecting Treatment Regress and Progress in Forensic Psychiatry: A Thematic Analysis - Askola, Riitta; Louheranta, Olavi; Seppänen, Allan (Frontiers in Psychiatry, 2022)
International variability and shifting trends in forensic psychiatry lead to gaps in national service provision and needs for service development. This study explores these needs through the subjective narratives of those involved in Finnish forensic services, either as forensic psychiatric patients, their parents, or service providers. Data was gathered by means of thematic interview and subjected to thematic analysis. Three main themes emerged: 1) pre-treatment challenges, 2) institutional/treatment-related concerns about therapeutic security and 3) adapting and recovery. The research highlights the need to develop forensic psychiatric services at three levels. First, it calls for increased risk awareness and risk assessment skills at the general psychiatric level. Second, it emphasizes the need for increased therapeutic engagement throughout the rehabilitative process. Third, it calls for structured and meaningful post-discharge aftercare. At all three levels, gradated security-aware standardization and patient triage in forensic services would help to develop and maintain an intact care pathway. This would decrease offending, marginalization, and suffering. Only then can we begin to meet the requirements of the WHO European Mental Health Action Plan. These findings can contribute to the development of international, standardized treatment models for clinical forensic psychiatric practices.